Adopsi Teknologi Penggunaan Layanan Online-to-Offline (O2O) Masyarakat Wilayah Pesisir - Dewi Sukmawati; Arizal Hamizar; Diar Muzna Tangke; Hanifah (Journal of Business Application, 2024)
This study aims to explore how consumers receive, understand, and utilize O2O services, considering challenges such as low digital literacy, risk perceptions, and the relevance of services to the local needs of coastal communities in Maluku. A qualitative approach was employed to delve into the experiences, perspectives, and motivations of the community in adopting O2O technology. Primary data were collected through in-depth interviews with purposively selected residents of Desa Grandeng, as well as participatory observation to understand the social and cultural contexts influencing consumer behavior. Data analysis was conducted using a thematic approach to identify key patterns affecting technology adoption, with particular attention to the unique local dynamics in coastal areas. The findings reveal that low digital literacy is the main barrier to adopting O2O technology in Desa Grandeng. Risk perceptions related to data security and the lack of outreach by service providers are also significant inhibiting factors. The limited relevance of O2O service features to local needs further restricts community acceptance. However, this study also identifies considerable potential to enhance technology adoption through community-based approaches, digital education programs, and the development of telecommunications infrastructure.